2003
DOI: 10.4049/jimmunol.170.7.3653
|View full text |Cite
|
Sign up to set email alerts
|

SS-A/Ro52, an Autoantigen Involved in CD28-Mediated IL-2 Production

Abstract: An autoantibody against SS-A/Ro52 (Ro52) is most frequently found in the sera of patients with Sjögren’s syndrome, systemic lupus erythematosus, and congenital heart block from anti-Ro52 Ab-positive mother. However, the physiological function of the autoantigen SS-A/Ro52 has not yet been elucidated. In this study, we describe the role of Ro52 protein in T cell activation. Overexpression of SS-A/Ro52 in Jurkat T cell resulted in enhanced IL-2 production following CD28 stimulation. Furthermore, transfection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…IRF4 is induced by T cell activation via TCR signaling, and the dramatic effects of IRF4 on Trim21 expression suggests that TRIM21 plays a role in T cell biology as previously suggested by Ishii et al (60). The higher expression level of IRF4 in B cells compared with T cells (http://www.immgen.org/databrowser/index.html) could explain the lower basal expression and weaker induction of Trim21 in B cells following IFN stimulation, because IRF4 can repress both the basal and IRF1-induced expression of Trim21.…”
Section: Discussionsupporting
confidence: 52%
“…IRF4 is induced by T cell activation via TCR signaling, and the dramatic effects of IRF4 on Trim21 expression suggests that TRIM21 plays a role in T cell biology as previously suggested by Ishii et al (60). The higher expression level of IRF4 in B cells compared with T cells (http://www.immgen.org/databrowser/index.html) could explain the lower basal expression and weaker induction of Trim21 in B cells following IFN stimulation, because IRF4 can repress both the basal and IRF1-induced expression of Trim21.…”
Section: Discussionsupporting
confidence: 52%
“…We showed that SSA directly binds and recruits ER to the promoter of target genes. Our findings of previously unidentified direct involvement of SSA in nuclear receptor-mediated transcription further emphasize its important regulatory roles in cellular physiology, in addition to its previously known ubiquitin-mediated proteasomal regulation of substrate proteins to activate signaling cascades such as NF-B, AP-1, and IRF3 (8,9).…”
Section: Discussionmentioning
confidence: 91%
“…Relevant to its clinical association with autoimmune diseases, SSA has been reported to play dual roles to regulate immune function. SSA enhances antibody-mediated immune responses to pathogens by increasing proinflammatory signaling pathways (8,9). SSA is also required to suppress cytokine production (10,11) as well as innate immune responses to intracellular double-stranded DNA (12).…”
mentioning
confidence: 99%
“…HEK293 cells were used to assay for human CD86 promoter activity following CD26-caveolin-1 interaction with Tollip and IRAK-1. Luciferase enzyme activity was determined using a luminometer (Promega), and relative light units were normalized to the protein amount determined with protein assay reagent according to the manufacturer's instructions (Pierce Biotechnology) (22,32,43).…”
mentioning
confidence: 99%